2013
DOI: 10.1186/1471-2393-13-126
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk estimation in women with a history of hypertensive pregnancy disorders at term: a longitudinal follow-up study

Abstract: BackgroundCardiovascular disease is associated with major morbidity and mortality in women in the Western world. Prediction of an individual cardiovascular disease risk in young women is difficult. It is known that women with hypertensive pregnancy complications have an increased risk for developing cardiovascular disease in later life and pregnancy might be used as a cardiovascular stress test to identify women who are at high risk for cardiovascular disease. In this study we assess the possibility of long te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…[38] In a short-term follow-up study that included mostly term and mild cases of hypertensive disease in pregnancy tested 2.5 years postpartum, the Reynolds Risk Score and the more traditional risk algorithms (SCORE and Framingham Risk Scores), we more or less equivalent in estimating predicted 10-year CVD risk. [39] It will be interesting the see whether or not these risk algorithms perform differently in cohorts with longer-term (>10 years) postpartum follow-up, and whether or not novel risk markers (in particular inflammatory markers) may prove to be beneficial in improving CVD risk prediction in models specifically designed to predict CVD in women with previous preeclampsia.…”
Section: Non-traditional Markers Of Cvd Riskmentioning
confidence: 99%
“…[38] In a short-term follow-up study that included mostly term and mild cases of hypertensive disease in pregnancy tested 2.5 years postpartum, the Reynolds Risk Score and the more traditional risk algorithms (SCORE and Framingham Risk Scores), we more or less equivalent in estimating predicted 10-year CVD risk. [39] It will be interesting the see whether or not these risk algorithms perform differently in cohorts with longer-term (>10 years) postpartum follow-up, and whether or not novel risk markers (in particular inflammatory markers) may prove to be beneficial in improving CVD risk prediction in models specifically designed to predict CVD in women with previous preeclampsia.…”
Section: Non-traditional Markers Of Cvd Riskmentioning
confidence: 99%
“…Hermes et al showed that women with a history of GH or preeclampsia at term had higher predicted 10‐ and 30‐year cardiovascular risk than did women with a history of uncomplicated pregnancies. 15 In a Japanese cohort study, GH was identified as a risk factor for hypertension, hypercholesterolemia, and diabetes in later life. 16 However, these studies failed to provide information about the cardiovascular risk of women with GH who later also developed hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors unique to women, such as preeclampsia and gestational diabetes that have been shown to increase a woman's future risk of CVD are not included in the women's equation (Hermes et al, 2013). Sibley, Blumenthal, Merz, and Mosca (2006) found based on the variables currently in the equation, unless a women is older than 70, she will usually not score high enough on the Framingham assessment to qualify for pharmacologic preventive interventions.…”
Section: Cardiovascular Risk Assessment For Women With a History Of Pmentioning
confidence: 99%